2021
DOI: 10.4049/jimmunol.1900217
|View full text |Cite
|
Sign up to set email alerts
|

IRF3 Signaling within the Mouse Stroma Influences Sepsis Pathogenesis

Abstract: IFN regulatory factor 3 (IRF3) is a transcription factor that is activated by multiple pattern-recognition receptors. We demonstrated previously that IRF3 plays a detrimental role in a severe mouse model of sepsis, induced by cecal ligation and puncture. In this study, we found that IRF3-knockout (KO) mice were greatly protected from sepsis in a clinically relevant version of the cecal ligation and puncture model incorporating crystalloid fluids and antibiotics, exhibiting improved survival, reduced disease sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 47 publications
3
22
0
Order By: Relevance
“…Previous reports from our lab showed that young adult IRF3-KO mice are significantly protected from sepsis induced by CLP in the absence 19 or presence 20 of clinical treatments. Absence of IRF3 was also found to protect mice from the systemic inflammatory response induced by liposome:DNA.…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations
“…Previous reports from our lab showed that young adult IRF3-KO mice are significantly protected from sepsis induced by CLP in the absence 19 or presence 20 of clinical treatments. Absence of IRF3 was also found to protect mice from the systemic inflammatory response induced by liposome:DNA.…”
Section: Introductionmentioning
confidence: 69%
“…CLP surgeries were performed per our prior reports. 20 , 24 Briefly, mice were anesthetized with isoflurane (2–2.5%) using a precision vaporizer. Buprenorphine-SR (1mg/kg; Zoopharm, Windsor, CO) was given s.c. prior to the surgery for pain management.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Supporting this observation, recent evidence has also shown that IRF3 acts principally within the stromal compartment to drive the networks TNF-α, IL-1β, and IL-6 in WT mice, whereas MCP-1 and IL-6 predominated in IRF3-KO mice. These studies show that IRF3KO affects macrophages by changing their capacity to produce IL-6 and MCP-1 [ 46 ]. Their results could explain our findings.…”
Section: Discussionmentioning
confidence: 99%